The Chromatin Remodelling Contributions of Snf2l in Cerebellar Granule Neuron Differentiation - Goodwin, Laura Rose (Université d'Ottawa / University of Ottawa, 2018)
Recent studies have uncovered de novo mutations of the gene encoding the chromatin remodelling protein Snf2l in patients with schizophrenia, Rett-like syndrome and intellectual disability. Snf2l and its closely related protein, Snf2h, play a critical role in embryonic and post-natal brain development. Murine models lacking functional Snf2h or Snf2l point to complementary activities of these remodelers; Snf2h cKO mice present with a significantly reduced cerebellum, while Snf2l Ex6DEL (exon 6 deleted) cerebella are larger than their wild-type counterparts. Granule neuron progenitors (GNPs) isolated from Ex6DEL cerebella display delayed cell cycle exit and hindered terminal differentiation compared to wild-type controls. Moreover, loss of Snf2l activity results in widespread transcriptome shifts which underlie the Ex6DEL GNP differentiation phenotype. In particular, key transcription factors are differentially expressed without Snf2l remodelling activity. We confirm that ERK pathway activation is misregulated in Ex6DEL GNPs, possibly in response to elevated fibroblast growth factor 8 (Fgf8) expression in these cultures. We find that Snf2l activity maintains the chromatin landscape throughout GNP differentiation, as Ex6DEL cultures have a global increase in chromatin accessibility. We suggest that Snf2l-mediated chromatin condensation is responsible for proper regulation of gene expression programs in GNP differentiation.
Keywords: ISWI; chromatin remodelling; granule neuron progenitor; cerebellum